Radicalism, Jihad and Terror - Yuminah Rahmatullah (Graduate Program of Pontianak Institute of Islamic Studies, 2017)
As an issue of complexity, radicalism does not stand alone. It has a political and ideological basis. Like an ideology that continues to bind, radicalism takes the path of religion to be able to justify all actions of anarchy. The case of today’s Islam as being synonymous with radicalism is apart of the complexcity of the issue. Religious radicalism is a prevalent phenomenon in the history religions. Radicalism is closely related to fundamentalism, which is marked by the return of society to the fundamentals of religion. Fundamentalism is a kind of ideology that makes religion the principle of life by society and individuals. Fundamentalism usually comes along with radicalism and violence when the freedom to return to religion is hindered by social and political circumstances surrounding the society. Islam recognizes jihad that is in some cases misunderstood. Jihad is different from radicalism and its derivatives of terrorism. Radicalism and terrorism tend to be destructive, uncompromising and closely related to violent behavior in the name of religion. Meanwhile jihad is a form of the totality of a Muslim's devotion to God, which is concerned not only with self-defense efforts, but a battle that has a theological legitimacy in which the martyrs are promised by God with various virtues and advantages. The association of jihad with terrorism today cannot be justified due to the fact that jihad in the sense of war (Qitâl) involves elements of violence that can be categorized as terrorism. It is the case that the use of violence in the name of religion in contemporary times is, in fact, due to political factors, which then seeks its legitimacy in religious teachings.